Application of SAK EMKM in the Food Stall Business “Bu Dina” - Yolanda, Nabila; Izzati, Dina; Alisha Zahrani, Vista; Franita, Riska (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This study aims to analyze the implementation of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) at Warung Makan Bu Dina, as well as the business owner's understanding of this standard and the challenges faced in its implementation. The method used was a descriptive qualitative approach with data collection through semi-structured interviews. The results showed that the level of awareness and understanding of business owners of SAK EMKM is still low. Some of the main obstacles identified include lack of education, lack of socialization regarding SAK EMKM, and resistance to changes in existing accounting practices. Nonetheless, the implementation of standardized financial statements can improve transparency and access to funding. The study concludes that to improve accounting practices among MSMEs, strategic interventions such as training and mentoring are needed. This is important so that MSMEs can utilize SAK EMKM as a tool to improve financial performance and competitiveness in the market. Thus, this study contributes to the understanding of accounting in the micro and small enterprise sector and offers a pathway for improved financial management in Indonesia.